Characteristics and immunoprotective functions of three cysteine proteases from Clonorchis sinensis - Shi, Yunliang; Li, Xiaoqin; Liang, Kai; Lu, Ting; Chen, Yu; Lai, Yashi; Li, Yaoting; Wei, Shuai; He, Shanshan; Tang, Lili; Liu, Dengyu; Li, Yanwen (Frontiers in Immunology, 2025)
IntroductionCysteine proteases from Clonorchis sinensis, including various proteins, are essential for its pathogenicity and serve as potential vaccine candidates. This study assesses the protective effects of three C. sinensis cysteine proteases (CsCP1-3).MethodsMice immunized with recombinant CsCP1-3 and adjuvants were subsequently infected with C. sinensis metacercariae after three immunization rounds. Liver damage was evaluated through hematoxylin and eosin (H&E), Masson’s trichrome, and immunohistochemical analyses. The levels of IgG1, IgG2a antibodies, and cytokines (IFN-g, IL-2, IL-4, and IL-10) were quantified by enzyme-linked immunosorbent assay (ELISA).ResultsRT-qPCR revealed that CsCP1-2 exhibited the highest expression in newly encysted larvae (NEL), while CsCP3 was predominantly expressed in adult stages. Immunohistochemical localization confirmed that CsCP1-3 are present in the eggshells, syncytial layers of metacercariae, NEL cuticle, and adult intestines. Histological and immunohistochemical analysis demonstrated that the rCsCP1-3-immunized group displayed reduced liver inflammation and biliary fibrosis compared to the control group. The rCsCP1-3 induced a progressive increase in specific IgG1 and IgG2a antibody titers by the second week post-immunization. In the CsCP1-2 group, cytokines IFN-g, IL-2, IL-4, and IL-10 were elevated relative to the control, with particularly high levels of IFN-g and IL-10 in CsCP1, indicating a strong mixed Th1/Th2 immune response. In contrast, the CsCP3 immunization group exhibited a transient increase in cytokines (IFN-g, IL-2, IL-4, and IL-10) three days postinfection, which subsided after one to two weeks.DiscussionThese findings suggest that CsCP1-3 elicit robust antibody and cellular immune responses, mitigating liver damage caused by C. sinensis infection. CsCP1, in particular, induces a potent mixed Th1/Th2 response, positioning it as a promising vaccine candidate.